Contextual Learning Strategies in English Subjects at Bilingual Primary School Muhammadiyah 1 Purwodadi - Budiman, Muhammad Arief; Untari, Mei Fita Asri; Murywantobroto, Murywantobroto; Listyarini, Ikha; Wahyuni, Sri (Universitas Dian Nuswantoro, 2023)
Abstract. Learning strategies need to be chosen by the teacher carefully so that the learning strategy chosen is not wrong and is under the conditions and circumstances of the students and the atmosphere of the class where the teacher is conducting the learning process. This research aims to analyze the learning strategies used by English teachers at the Bilingual elementary school Muhammadiyah 1 Purwodadi. This research is a qualitative descriptive study using interviews, questionnaires, and observation data collection methods. The research results show that learning English with contextual learning can run smoothly, and this statement is supported by the results of the triangulation of 3 data. Interview data shows that the teacher succeeded in making learning plans using contextual learning steps. Observation data shows that teachers are successful in carrying out learning using contextual learning. The results of the questionnaire showed that the students liked the contextual learning that the teacher applied in the English class. The conclusion is that contextual learning strategy can make the English language learning process at the Bilingual Elementary School Muhammadiyah 1 Purwokerto run smoothly.Keywords: bilingual; contextual learning; elementary school; English; strategyAbstrak. Strategi pembelajaran perlu dipilih oleh guru dengan hati-hati dan cermat agar strategi pembelajaran yang dipilih tidak salah dan sesuai dengan kondisi dan keadaan peserta didik dan suasana kelas tempat guru tersebut mengadakan proses pembelajaran. Penelitian ini bertujuan untuk menganalisis strategi pembelajaran yang digunakan oleh guru bahasa inggris di sekolah dasar Bilingual Muhammadiyah 1 Purwodadi. Penelitian ini merupakan deskriptif kualitatif dengan metode pengumpulan data wawancara, angket atau kuesioner, dan observasi atau pengamatan. Hasil penelitian menunjukkan pembelajaran bahasa inggris dengan contextual learning bisa berjalan dengan lancar dimana pernyataan ini didukung dari hasil triangulasi 3 data. Data hasil wawancara menunjukkan bahwa guru berhasil membuat perencanaan pembelajaran dengan langkah-langkah pembelajaran kontekstual learning. Data pengamatan menunjukkan bahwa guru berhasil menjalankan pembelajaran dengan menggunakan pembelajaran kontekstual. Hasil angket menunjukkan bahwa para siswa menyenangi pembelajaran kontekstual yang diaplikasikan guru di dalam kelas bahasa Inggris. Kesimpulan yang didapat adalah bahwa strategi pembelajaran kontekstual mampu membuat proses pembelajaran bahasa Inggris di Sekolah Dasar Bilingual Muhammadiyah 1 Purwokerto berjalan lancar.Kata kunci: bahasa Inggris; dwibahasa; pembelajaran kontekstual; sekolah dasar; strategi